Significance of PSI re-use - Fodorné Zagyi, Orsolya (Acta Agraria Debreceniensis, 2016)
The prime aim of this study is draw attention to the importance of the issue connection with PSI reuse, to give a survey of the attepts carried out so far, legal impoudments. With the help of this we are trying to systematize conceptual basic as well as to expand the fields researched. Regarding PSI reuse the 89/2003 Directives of EU serve far the prime factor, as well as the LXIII. act of 2012. Which is the adoptation of the directive in Hungary including its modfications.In Hungary a new governmental strategy is being formed, which would make the widespread use of PSI possible. Doing so via their reuse it would contribute to establishing new products and services. By this means it would greathy support the improving competitivness of the Hungarian economy.